3D Pd/Co core–shell nanoneedle arrays as a high-performance cathode catalyst layer for AAEMFCs. Issue 23 (5th April 2018) - Jia, Jia; Yu, Hongmei; Gao, Xueqiang; Chi, Jun; Zeng, Yachao; Qin, Bowen; Yao, Dewei; Song, Wei; Shao, Zhigang; Yi, Baolian
Abstract : A novel ordered Pd/Co nanoneedle array was used as a cathode in an AAEMFC and delivered a higher power density than that of conventional MEA. Abstract : A novel cathode architecture using vertically aligned Co nanoneedle arrays as an ordered support for application in alkaline anion-exchange membrane fuel cells (AAEMFCs) has been developed. The Co nanoneedle arrays were directly grown on a stainless steel sheet via a hydrothermal reaction and then a Pd layer was deposited on the surface of the Co nanoneedle arrays using a vacuum sputter-deposition method to form Pd/Co nanoneedle arrays. After transferring the Pd/Co nanoneedle arrays to an AAEM, a cathode catalyst layer was formed. Without the use of an alkaline ionomer, the AAEMFC with the prepared cathode catalyst layer showed an enhanced performance with ultra-low Pd loading of down to 33.5 μg cm −2, which is much higher than the conventionally used cathode electrode with a Pt loading of 100 μg cm −2 . This is the first report where three-dimensional Co nanoneedle arrays have been used as the cathode support in an AAEMFC, which is able to deliver a higher power density without an alkaline ionomer than that of conventional membrane electrode assembly (MEA).